Sektor Penjaminan Halal Pada Industri Pariwisata - Naila Tasya; Malahayatie (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2024)
This article discusses in detail the concept of halal assurance, challenges and opportunities in the tourism industry, as well as implications for relevant stakeholders. Through a qualitative approach and case studies from various countries, this article aims to provide a comprehensive understanding of the importance and implementation of halal assurance in tourism. This research also highlights the role of government, industry players and certification bodies in creating an ecosystem that supports halal tourism. The results of this article's discussion include an in-depth analysis of the effectiveness of halal guarantees in increasing the attractiveness of tourist destinations, identification of the main challenges in implementing halal guarantees, as well as strategies that can be adopted by various stakeholders to overcome these challenges. The findings from this research also show that the existence of good halal guarantees can increase the trust of Muslim and non-Muslim tourists in tourist destinations, as well as support local economic growth through increasing tourist visits. The recommendations provided in this article can be a reference for policy makers and practitioners in developing a sustainable halal tourism industry. In a global context, the increase in the number of Muslim tourists has a significant impact on various tourist destinations. Therefore, tourist destinations that can provide facilities and services in accordance with halal principles have great potential to attract more tourists. The implementation of halal guarantees does not only cover food and drinks, but also other aspects such as accommodation, entertainment and health services.